2015
DOI: 10.1093/ecco-jcc/jjv194
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Elderly-onset Ulcerative Colitis: Results from a Territory-wide Inflammatory Bowel Disease Registry

Abstract: Elderly-onset UC patients are increasing in number. These patients have higher risk of opportunistic infections, hospitalisation, colorectal cancer, and mortality than non-elderly-onset patients. Management and therapeutic strategies in this special group need careful attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 52 publications
8
74
0
3
Order By: Relevance
“…It is also increasingly recognised as secondary infection increasing the risk of more severe disease course and colectomy . In addition, with the increasing incidence of elderly onset UC, the incidence of colonic diverticulitis will also increase in the UC population . The VOC analyses and statistical model used in the present study, did show that the discriminating VOCs could also distinguish between UC inflammation and non‐UC related colonic inflammation.…”
Section: Discussionmentioning
confidence: 50%
“…It is also increasingly recognised as secondary infection increasing the risk of more severe disease course and colectomy . In addition, with the increasing incidence of elderly onset UC, the incidence of colonic diverticulitis will also increase in the UC population . The VOC analyses and statistical model used in the present study, did show that the discriminating VOCs could also distinguish between UC inflammation and non‐UC related colonic inflammation.…”
Section: Discussionmentioning
confidence: 50%
“…Particular care should be taken when dealing with infection in this subgroup of high‐risk IBD patients. In our recent study we also found that elderly‐onset UC patients had a higher risk of developing CMV and C . difficile infections, despite comparable exposure to corticosteroids and immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 65%
“…We identified all patients newly diagnosed with IBD between January 2010 and December 2012 in the Hong Kong IBD Registry. The details of the registry had been reported previously . Briefly, it is a territory‐wide IBD registry including 13 regional hospitals of the Hospital Authority of Hong Kong SAR, China, the sole public healthcare provider for 7.2 million local residents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a territory-wide study in the Chinese population showed that elderly-onset UC patients are increasing and they have a higher risk of opportunistic infections, hospitalisation, colorectal cancer (CRC), and mortality than non-elderly-onset patients. Therefore, management and therapeutic strategies in this special group need special attention [45]. …”
Section: Prognosismentioning
confidence: 99%